Ionophore susceptibility of Eimeria zaria: First characterisation in a cryptic Eimeria species of chickens - Marta Raffaelli; José Manuel Jaramillo-Ortiz; Marili Vasilogianni; Melanie C. Hay; Daniel Ngugi; Caela Burrell; Virginia Marugan-Hernandez; Stefania Perrucci; Dong Xia; Damer P. Blake (Veterinary Parasitology, 2026)

Changes in equine hindgut bacterial populations during oligofructose‐induced laminitis - G. J. Milinovich; D. J. Trott; P. C. Burrell; A. W. Van Eps; M. B. Thoefner; L. L. Blackall; R. A. M. Al Jassim; J. M. Morton; C. C. Pollitt (Environmental Microbiology, 2006)
Summary In the horse, carbohydrate overload is thought to play an integral role in the onset of laminitis by drastically altering the profile of bacterial populations in the hindgut. The objectives of this study were to develop and validate microbial ecology methods to monitor changes in bacterial populations throughout the course of experimentally induced laminitis and to identify the predominant oligofructose‐utilizing organisms. Laminitis was induced in five horses by administration of oligofructose. Faecal specimens were collected at 8 h intervals from 72 h before to 72 h after the administration of oligofructose. Hindgut microbiota able to utilize oligofructose were enumerated throughout the course of the experiment using habitat‐simulating medium. Isolates were collected and representatives identified by 16S rRNA gene sequencing. The majority of these isolates collected belonged to the genus Streptococcus , 91% of which were identified as being most closely related to Streptococcus infantarius ssp. coli . Furthermore, S . infantarius ssp. coli was the predominant oligofructose‐utilizing organism isolated before the onset of lameness. Fluorescence in situ hybridization probes developed to specifically target the isolated Streptococcus spp. demonstrated marked population increases between 8 and 16 h post oligofructose administration. This was followed by a rapid population decline which corresponded with a sharp decline in faecal pH and subsequently lameness at 24–32 h post oligofructose administration. This research suggests that streptococci within the Streptococcus bovis / equinus complex may be involved in the series of events which precede the onset of laminitis in the horse.

Effect of deletion and the site of insertion in double copy anti-tat retroviral vectors: viral titres and production of anti-tat mRNA - J. M. Carr; J. K. Calvert; R. Kumar; C. J. Burrell; P. Li (Archives of Virology, 2001)

HIV DNA integration during cell-to-cell transmission of infection: evidence for partially integrated DNA structures in acutely infected cells - T. Kok; P. Li; C. J. Burrell (Archives of Virology, 2001)

Further characterization of HIV RNA synthesis early after cell-to-cell transmission infection - T-W. Kok; P. Li; C. J. Burrell (Archives of Virology, 1998)

AZT blocks down-regulation of IL-2 and IFN-γ gene expression in HIV acutely infected cells - J. Fan; P. Li; T.-W. Kok; C. J. Burrell (Archives of Virology, 1997)

Establishment of persistent HIV-1 infection in vitro is accompanied by reduction of NF-?B activity - X. Zhang; P. Li; C. J. Burrell (Archives of Virology, 1994)

Isolation of reovirus type 2 from respiratory tract of sheep - D. R. Snodgrass; C. Burrells; P. W. Wells (Archives of Virology, 1976)

Immunoglobulins, antibodies and inhibitors of Parainfluenza 3 virus in respiratory secretions of sheep - W. D. Smith; P. W. Wells; C. Burrells; A. McL Dawson (Archives of Virology, 1975)